Jak zaradzić zjednoczeniu? Szkockie strategie oporu wobec projektu unii 1707 r. na podstawie The Lockhart Papers George’a Lockharta z Carnwath .......... 107 - Cholewa, Karolina (Od Sumeru do zimnej wojny, 2025)
HOW TO PREVENT THE UNION? SCOTTISH STRATEGIES OF RESISTANCE TO THE 1707 UNION PROJECTBased on The Lockhart Papers by George Lockhart of Carnwath The author of this article focuses on presenting the resistance strategies undertaken by Scottish society in 1706. Their aim was to manifest opposition to the proposed Act of Union, which led to the formation of the United Kingdom. The paper begins with a characterization of the key events that led to the union negotiations. Subsequently, the author focuses on introducing the figure of George Lockhart, as well as discussing the methods of working on his writings. The main part of the article is dedicated to presenting three primary resistance strategies: street riots, petition campaigns, and attempts to incite armed rebellion. Each section is accompanied by reflections on the mentality of the Scots and the challenges they faced in the 18th century. The work concludes with an attempt to resolve whether the Union of 1707 and the subsequent loss of Scotland’s sovereignty equated to the demise of national identity, or whether it merely marked the beginning of its new dimension, which has been evolving to this day.